Membrane capacitive deionization for low-salinity desalination in the reclamation of domestic wastewater effluents. (November 2019) - Lee, Mengshan; Fan, Chen-Shiuan; Chen, Yu-Wu; Chang, Kuang-Chih; Chiueh, Pei-Te; Hou, Chia-Hung
Abstract: This study aims to investigate the feasibility of desalinating secondary effluent from a domestic wastewater treatment plant (DWTP) using membrane capacitive deionization (MCDI) for reclamation purposes. The desalination performance of a MCDI stack with 10 pairs of 20 cm × 20 cm activated carbon electrodes was evaluated in single-pass mode. As evidenced, the MCDI stack outperformed the capacitive deionization stack. The water quality characteristics of the inflows and product water were also analyzed. Our results revealed that MCDI can effectively remove undesired ions such as calcium and nitrate from the DWTP effluent for water reclamation. In particular, the solution conductivity of the product water was observed to be as low as 1.27 μS/cm. Removal of the ions was easily performed by the electrostatic field-assisted deionization process. The use of MCDI for low-salinity wastewater reclamation demonstrated favorable energy performance with a low volumetric energy input and a molar energy input of 0.12 kWh/m 3 and 0.03 kWh/mole, respectively; and the energy efficiency of this system is expected to be further improved by energy recovery or incorporation of energy-producing processes. These results are indicative of the benefits of using MCDI as part of the treatment processes for the reclamation of wastewater with low salinity. Highlights: A scale-up MCDI system was developed to desalinate secondary effluent. Ion-exchange membranes help to improve desalination and energy performance. Removal efficiencies of 83% for TDS and 92% for water hardness were achieved. The energy performance and implications of the MCDI system were addressed. MCDI is an energy efficient process for reclamation of wastewater with low salinity.